2014
DOI: 10.1039/c4cp03036b
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic DFT calculations of magnetic moments of pristine and thiolated Mn@Aux (x = 6, 12)

Abstract: In this work we present the results of relativistic DFT calculations of magnetic moments for manganese inserted into a gold ring (Mn@Au6) or a cage-like structure (Mn@Au12) both pristine and n-thiolated. Optimization has been carried out to obtain different isomers always favouring the endohedral gold clusters with Mn inside. For the total magnetic moment (from electronic population analysis) verification of the jellium model has been performed in each case. It is concluded that the magnetic moments arise larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Endohedral M@Au 12 cage clusters with M = 3d, 4d, and 5d elements have been theoretically explored by many groups 121,[674][675][676][677][678][679]688,689 DFT calculations with PBE functional were performed on M@ Au 12 (M = 3d elements) 121 and large local magnetic moments of over 2 μ B were found for M = Mn, Fe, and Co. It was argued that the orbital magnetism of these 3d doped icosahedral clusters (up to about 0.65 μ B , aligned either antiparallel or parallel to the magnetic spin moment) can be rationalized by the relativistic effects together with a superatom picture.…”
Section: Doped Au Cagesmentioning
confidence: 99%
“…Endohedral M@Au 12 cage clusters with M = 3d, 4d, and 5d elements have been theoretically explored by many groups 121,[674][675][676][677][678][679]688,689 DFT calculations with PBE functional were performed on M@ Au 12 (M = 3d elements) 121 and large local magnetic moments of over 2 μ B were found for M = Mn, Fe, and Co. It was argued that the orbital magnetism of these 3d doped icosahedral clusters (up to about 0.65 μ B , aligned either antiparallel or parallel to the magnetic spin moment) can be rationalized by the relativistic effects together with a superatom picture.…”
Section: Doped Au Cagesmentioning
confidence: 99%
“…Theoretical methods based on density functional theory (DFT) are widely used to treat the structural and electronic properties of metal clusters, and especially for heavier transition-metals (TM), the inclusion of relativistic effects through spin–orbit coupling (SOC) has been debated. 4,6,15 On the other hand, turning attention to improvements in the description of long range electronic correlation effects at the DFT and CCSD(T) levels, which is commonly fulfilled by the van der Waals (vdW) corrections, is essential by concerning the 2D/3D stability competition for Ag 13 and Au 13 metal clusters. In this context, it is important to mention that the employment of single and double CCSD(T) as a high-level ab initio method 16 – taking into account the inclusion of a quasi-complete basis set with relativistic effects and vdW correction – is not trivial for systematic study especially due to the high computational cost required.…”
Section: Introductionmentioning
confidence: 99%
“…Again, the I h configuration was found as the lowest energy structure for these clusters from both DFT calculations considering I h , O h , and D 5 h structures and the comparison between the simulated photoelectron spectra and the measured ones. Other calculations on 18-electron systems of M@Au 12 with M = Cr, Mn + , Zr 2– , Nb – , Mo, Tc + , Ru 2+ , Hf 2– , Ta – , W, Re + , and Os 2+ were also studied. Most of them have the lowest energy structures with I h symmetry, while Cr@Au 12 , Tc@Au 12 + , and Mn@Au 12 + have O h , O h , and T d GSs, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The energies of the I h structures were compared with those of the O h structures for M@Au 12 clusters M = V, Cr, Mn, Nb, Mo, Ta, W, and Re by Zhou et al Among them, the Cr/Mn/Mo/W/Re@Au 12 clusters were found to have icosahedral GSs. Raggi et al showed that the Mn@Au 12 cluster prefers to possess a high-spin magnetic O h structure (5 μ B ) rather than a low-spin I h structure (1 μ B ). Long et al found cuboctahedral isomers of the M@Au 12 (M = Hf–Hg) clusters to be more stable than icosahedral isomers except for W@Au 12 .…”
Section: Introductionmentioning
confidence: 99%